2015
DOI: 10.1167/iovs.15-16602
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Optic Nerve Protrusion Measured by OCT and MRI and Papilledema Severity

Abstract: Significant linear correlation between OCT and MRI measurements of NPL supports the reliability of the OCT-based measurements of NPL in papilledema. Significant association between the papilledema grade and OCT- and MRI-based measurements of NPL highlights the potential of NPL as an objective and more sensitive marker of papilledema severity than the Frisen scale.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…We and other authors have shown that size/volume of the ONH and thickness of the retinal nerve fiber layer (RNFL) can be increased even in subtle IIH without papilledema (IIHWOP). OCT measures are correlated with cerebrospinal fluid (CSF) pressure and Frisén grading of papilledema . In contrast to CSF pressure measure and fundus assessment, OCT is a non‐invasive, sensitive and objective in‐vivo method.…”
Section: Introductionmentioning
confidence: 99%
“…We and other authors have shown that size/volume of the ONH and thickness of the retinal nerve fiber layer (RNFL) can be increased even in subtle IIH without papilledema (IIHWOP). OCT measures are correlated with cerebrospinal fluid (CSF) pressure and Frisén grading of papilledema . In contrast to CSF pressure measure and fundus assessment, OCT is a non‐invasive, sensitive and objective in‐vivo method.…”
Section: Introductionmentioning
confidence: 99%
“…These include swelling of the optic nerve head due to axoplasmic flow stasis, which is an important diagnostic sign for increased ICP, (1) globe flattening, peripapillary deformation and expansion of the optic nerve sheath, all presumably due to mechanical pressure of the CSF in the nerve sheath. Ophthalmic and neuro-images of the optic nerve and surrounding globe have demonstrated differences in optic nerve head volume (ONHV), globe flattening, and peripapillary Bruch's membrane displacement (pBMd) between high and normal ICP states, and, on this basis they are candidates as diagnostic markers of high ICP states (25).…”
Section: Introductionmentioning
confidence: 99%
“…Common MRI findings of papilledema include (1) enlargement of the optic nerve sheath, (2) flattening of the posterior sclera, (3) protrusion of the papilla into the globe, and (4) optic nerve tortuosity (Fig 1). 1–3,12–16 Although raised ICP and papilledema are diagnosed clinically, further delineating the globes, optic nerves, and optic nerve sheaths should be achieved using dedicated orbital scans, particularly in suspected IIH. Imaging has become recognized for its role in the diagnosis of IIH, with its typical signs, and not only for exclusion of other pathologies 15 .…”
Section: Mri Of the Orbitsmentioning
confidence: 99%